2020
DOI: 10.1021/acs.molpharmaceut.0c00131
|View full text |Cite
|
Sign up to set email alerts
|

Chemoproteomic Identification of Serine Hydrolase RBBP9 as a Valacyclovir-Activating Enzyme

Abstract: Prodrug discovery and development in the pharmaceutical industry have been hampered by a lack of knowledge of prodrug activation pathways. Such knowledge would minimize the risks of prodrug failure by enabling proper selection of preclinical animal models, prediction of pharmacogenomic variability, and identification of drug−drug interactions. Technologies for annotation of activating enzymes have not kept pace with the growing need. Activity-based protein profiling (ABPP) has matured considerably in recent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…These results show that V-Gem undergoes extensive activation in intestinal epithelial cells as intact prodrug accounted for < 12% of total drug found in portal plasma. This observation is consistent with other work reporting extensive activation of amino acid ester prodrugs in mouse and rat intestinal epithelium [30,[37][38][39]. Additionally, perfusion experiments were performed showing gemcitabine is quite stable in the intestinal lumen (< 1% of perfused gemcitabine found in outlet samples as dFdU) but undergoes first-pass metabolism in the intestinal enterocytes, as evidenced by the appearance of dFdU in portal plasma, accounting for about 30% of total drug.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results show that V-Gem undergoes extensive activation in intestinal epithelial cells as intact prodrug accounted for < 12% of total drug found in portal plasma. This observation is consistent with other work reporting extensive activation of amino acid ester prodrugs in mouse and rat intestinal epithelium [30,[37][38][39]. Additionally, perfusion experiments were performed showing gemcitabine is quite stable in the intestinal lumen (< 1% of perfused gemcitabine found in outlet samples as dFdU) but undergoes first-pass metabolism in the intestinal enterocytes, as evidenced by the appearance of dFdU in portal plasma, accounting for about 30% of total drug.…”
Section: Discussionsupporting
confidence: 91%
“…Following intravenous V-Gem administration, the prodrug rapidly disappeared from plasma with a T 1/2 of 3.7 min, while gemcitabine rapidly appeared in plasma, with the gemcitabine T max occurring in the first sample (2 min) for all mice. Two enzymes, RBBP9 and the biphenyl hydrolase like enzyme (BPHL), have previously been shown to catalyze V-Gem activation in vitro via V-Gem incubations with these recombinant human enzymes [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The rapid and quantitative identification of functional and potentially druggable amino acids is a central goal of mass spectrometry-based chemoproteomics. [1] While chemoproteomics has been successfully applied to assay a wide range of nucleophilic amino acid side chains, including serine, [2][3][4] lysine, [5] tyrosine, [6] methionine, [7] glutamate and aspartate, [8][9][10] the thiol side chain of reduced cysteine residues [11,12] has emerged as a favored residue for such studies. Cysteine's prominence in chemoproteomic studies can be rationalized by both the unique chemistry of the cysteine thiol and the recent resurgence of cysteine-reactive compounds as useful chemical probes and blockbuster drugs.…”
Section: Introductionmentioning
confidence: 99%
“… 55 A recent proteomics study identified another hydrolase capable of activating valacyclovir, namely, retinoblastoma-binding protein 9 (RBBP9). 36 l -val-DAC is also a substrate of BPHL and PEPT1 and features significantly improved bioavailability and rapid intestinal activation. 34 , 56 The activity of BPHL on l -val-DAC (91 600 pmol/min/μg) was extracted from the V 0 versus [S] plot of BPHL-mediated l -val-DAC hydrolysis reported in a previous study.…”
Section: Resultsmentioning
confidence: 99%